Community response to noise: research in Central, Eastern and South-Eastern Europe and Newly Independent States - Jeram, Sonja; Lekaviciute, Jurgita; Krukle, Zanda; Argalasova-Sobotova, Lubica; Ristovska, Gordana; Paunovic, Katarina; Pawlaczyk-Luszczynska, Malgorzata (Medknow, 2013)
The systems of public complaints on environmental noise were reviewed in seven countries of Central and Eastern Europe (CEE), South-East Europe (SEE), and Newly Independent States (NIS). Public complaints remain an important issue due to differences in public sensitivity to noise and due to several cases where a measurement of noise intensity does not give a satisfying solution to the problem. The unresolved problem remaining in the residential neighborhoods is the noise from pubs and restaurants that are open until late in the night. In our review, we compiled information on the institutions responsible for the implementation of environmental noise legislation and organizations that are responsible for dealing with public complaints. Information on activities for increasing public awareness on hazards rising from environmental noise and the role of civil initiative was explored. In seven countries, and among them, Slovenia, Lithuania, Latvia, Slovakia, The Former Yugoslav Republic of Macedonia, Serbia, and Poland, the responsibilities and duties are shared among different institutions at national and regional levels, depending on the noise source. The problem of gathering information on complaints and using it for improving the wellbeing and health of citizens remains often difficult and unsolved.
Keywords: complaints; environmental noise; municipalities; responsible authorities; wellbeing